Aerobic production and utilization of lactate satisfy increased energy demands upon neuronal activation in hippocampal slices and provide neuroprotection against oxidative stress - Schurr, Avital; Gozal, evelyne (Frontiers in Pharmacology, 2012)
Ever since it was shown for the first time that lactate can support neuronal function in vitro as a sole oxidative energy substrate, investigators in the field of neuroenergetics have been debating the role, if any, of this glycolytic product in cerebral energy metabolism. Our experiments employed the rat hippocampal slice preparation with electrophysiological and biochemical methodologies. The data generated by these experiments a) support the hypothesis that lactate, not pyruvate, is the end product of cerebral aerobic glycolysis; b) indicate that lactate plays a major and crucial role in affording neural tissue to respond adequately to glutamate excitation and to recover unscathed post-excitation; c) suggest that neural tissue activation is accompanied by aerobic lactate and NADH production, the latter being produced when the former is converted to pyruvate by mitochondrial lactate dehydrogenase (mLDH); d) imply that NADH can be utilized as an endogenous scavenger of reactive oxygen species (ROS) to provide neuroprotection against ROS-induced neuronal damage.